A novel adjuvant drug-device combination tissue scaffold for radical prostatectomy. (1st January 2019) - Paliashvili, Ketevan; Di Maggio, Francesco; Ho, Hei Ming Kenneth; Sathasivam, Sanjayan; Ahmed, Hashim; Day, Richard M.
Abstract: Prostate cancer is a leading cause of death in men and despite improved surgical procedures that aid tumor resection, the risk of recurrence after surgery as a result of positive resection margins remains significant. Adjuvant chemotherapy is often required but this is associated with toxicity. Improved ways of delivering highly toxic chemotherapeutic drugs in a more controlled and targeted manner after the prostate has been removed during surgery could reduce the risk of recurrence and avoid systemic toxicity. The aim of this study was to develop a novel drug-device combination tissue scaffold that can be used to deliver the chemotherapeutic agent, docetaxel, into the tissue cavity that is created following radical prostatectomy. The device component investigated consisted of highly porous, poly(dl -lactide-co-glycolide) microparticles made using thermally induced phase separation. A facile method was established for loading docetaxel with high efficiency within one hour. Sustained drug release was observed from the microparticles when placed into a dynamic system simulating tissue perfusion. The drug released from the microparticles into perfusates collected at regular time intervals inhibited colony formation and exhibited sustained cytotoxicity against 3D spheroids of PC3 prostate cancer cells over 10 days. In conclusion, this study demonstrates the concept of combining docetaxel with the biodegradable microparticles at the point of care is technically feasible for achieving an effective drug-device combination tissue scaffold. This approach could provide an effective new approach for delivering adjuvant chemotherapy following radical prostatectomy.